Terms of endearment [videorecording (DVD)] - Brooks, James L.; MacLaine, Shirley, 1934-; Nicholson, Jack; Winger, Debra, 1955-; McMurtry, Larry (Paramount, 2000)
A comedy-drama about the evolving 30+ year relationship between a mother and daughter.